Challenges of sexually transmitted infections and sexual health among people who inject drugs. Issue 1 (February 2022) - Dumchev, Kostyantyn
Abstract : Purpose of review: This review provides a summary of recently published research on sexually transmitted infections (STI) and related behaviors among people who inject drugs (PWID), covering three major areas: sexual behavior and its role in STI transmission among PWID, multilevel factors associated with STI risk, and strategies addressing sexual health of PWID. This review is timely given the growing priority of combination prevention approaches and integrated care for PWID. Recent findings: Modern research improves the understanding that PWID have an increased risk of STI, which varies by gender, setting, type of substance used, and presence of mental disorders. Major socioeconomic and structural factors, specific and nonspecific to PWID, facilitate inequality and sexual risk behavior. Sexual transmission continues to contribute substantially to the spread of bloodborne infections among PWID, accounting for at least 10% of new HIV cases according to epidemiological modeling. Despite the substantial evidence that behavioral interventions can improve sexual health and reduce sex-related risks among PWID, there is a research-practice gap, reflected in the scarcity of implementation studies published recently. Summary: Integration of sexual health into prevention programs for PWID is essential to curb transmission of STI, including HIV, among PWID and their sexual partners.